Estudo etnobotânico das plantas medicinais utilizadas pela população de Riachinho, TO: relatos sobre seu uso na prevenção e no tratamento da COVID-19 - FERREIRA, Kelrilane de Morais (Universidade Federal do Tocantins, 2023)
The work aimed to carry out ethnobotanical studies of medicinal plants used by the population of Riachinho, TO for different diseases, highlighting the prevention and treatment therapies of COVID-19. Identify the most used medicinal plants, the parts used, forms of preparation, method of acquisition, source of indications and know the plants most used in the prevention and treatment of COVID-19. 64 residents of the 16 streets present in the city of Riachinho, TO were interviewed. The most cited species for several diseases were Lippia alba (Mill.) N.E. Br. ex Britton & P. Wilson (erva cidreira), Mentha villosa Briq. (mint), Aloe vera L. Baker (aloe), Rosmarinus officinalis L. (Mill.) Rouy. (rosemary). The most used plants in the prevention and treatment of coronavirus were Plectranthus barbatus (boldo) with 36.76% of citations, Curcuma longa L. (saffron) with 16.18%, and Citrus limon L. (limon) with 14.71%. Regarding the part of the plant most used by the interviewees, it was the leaves. The most used form of preparation of medicinal species stands out as the form of tea. Friends are the greatest influencers for the use of plants as well as for prevention as for the treatment of COVID-19, where the main source of indication is family members. Therefore, the population of Riachinho, TO, use medicinal plants in their daily lives, indicated for the treatment of the respiratory and digestive systems and for cancer. The indications cited by the interviewees partially coincide with data from the scientific literature; as for the species mentioned for the prevention and treatment of COVID-19, only Allium sativum L. has scientific evidence